2010
DOI: 10.2174/1874279301004010101
|View full text |Cite
|
Sign up to set email alerts
|

EBV-Associated Malignancies

Abstract: Epstein-Barr virus (EBV) infection has been implicated in the aetiopathogenic mechanisms of several neoplastic and non-neoplastic disorders. Although the precise mechanisms of the tumourigenic actions of EBV have not yet been fully elucidated, this virus has been strongly linked to subtypes of Hodgkin's and non-Hodgkin's lymphomas (especially Burkitt's lymphoma), HIV/AIDS lymphomas, nasopharyngeal carcinoma and gastric carcinoma, among several others. The fact that persistent infections occur in greater than 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Latency II (also called the “default program,” characterized by LMP1+/EBNA2−) is expressed in cells entering the germinal center reaction that mediates antibody affinity maturation whereas memory cells express latency I (or the “latency program,” characterized by LMP1−/EBNA2−) [40]. Although PTLD has been associated with latency III expression, this profile is probably only required in the early phases of B-cell infection as viral gene expression may vary within and between tumors [41]. …”
Section: The Epstein-barr Virus (Ebv) Exploits B-cell Differentiatmentioning
confidence: 99%
“…Latency II (also called the “default program,” characterized by LMP1+/EBNA2−) is expressed in cells entering the germinal center reaction that mediates antibody affinity maturation whereas memory cells express latency I (or the “latency program,” characterized by LMP1−/EBNA2−) [40]. Although PTLD has been associated with latency III expression, this profile is probably only required in the early phases of B-cell infection as viral gene expression may vary within and between tumors [41]. …”
Section: The Epstein-barr Virus (Ebv) Exploits B-cell Differentiatmentioning
confidence: 99%
“…On the other hand, in immunodepressed patients as well as in transplant recipients undergoing immunosuppression, CTLs are immobilized, allowing for the proliferation and immortalization of infected B cells [ 1 ]. EBV has been demonstrated to be involved in the development of numerous malignancies, both in immunocompetent hosts and in immunocompromised individuals [ 2 ]. The first association was with the endemic Burkitt’s lymphoma.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Studies have shown a strong association between EBV and the development of both nasopharyngeal carcinoma and hematologic malignancies, such as extranodal NK/T-cell lymphoma, nasal type, Burkitt's and Hodgkin's lymphoma. 5 Crucial in elucidating this case were the positive laboratory results, improvement with antibiotics, and corroborating immunohistochemical stain highlighting T pallidum. While a synchronous malignancy still cannot be excluded, close clinical follow-up has shown no further suspicious findings.…”
Section: Discussionmentioning
confidence: 67%
“…Studies have shown a strong association between EBV and the development of both nasopharyngeal carcinoma and hematologic malignancies, such as extranodal NK/T-cell lymphoma, nasal type, Burkitt’s and Hodgkin’s lymphoma. 5…”
Section: Discussionmentioning
confidence: 99%